Pengaruh Media Pembelajaran Video Terhadap Peningkatan Motivasi Belajar Siswa pada Mata Pelajaran PPKN di SMP IT Nur Al Rahman Cimahi - Eneng Martini; Nisa Nur Aliza (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In the process of learning activities, teachers should be required to be able to choose the right learning media in delivering learning materials to students, so that students more easily understand and recall the subject matter presented by the teacher, and create an attraction for students to be more active in participating in the learning process. teach. Therefore, I am interested in researching the Effect of Video Learning Media on Increasing Student Learning Motivation in Civics Subjects at SMP IT Nur Al Rahman Cimahi. The problems that will be discussed in this research are; 1) how to use video learning media in Civics subjects; 2) how is the motivation of students in PPKn subjects; 3) how much influence the use of video media in increasing students' motivation in learning Civics. The purpose of the study was to determine the effect of video learning media on students' learning motivation. The research method used in this study is a quantitative method. The sampling technique is by random sampling. The results of the study are 1) The value for the video learning media variable (X) is 49.02. The classification is said that the video learning media variable (X) belongs to the